Exploring informed choice in preconception reproductive genetic carrier screening by using a modified Multidimensional Measure of Informed Choice. Issue 11 (November 2022) - Van Steijvoort, Eva; Peeters, Hilde; Vandecruys, Hilde; Verguts, Jasper; Peeraer, Karen; Matthijs, Gert; Borry, Pascal
Abstract: Objectives: To explore informed choice in reproductive genetic carrier screening (RGCS). Methods: Women visiting a gynaecologist practice in Flanders (Belgium) were asked to consider participation in a study where RGCS was offered for free to them and their male partner. A modified Multidimensional Measure of Informed Choice was used to determine whether couples who opted for RGCS made an informed choice. In addition, we assessed risk perception, feelings towards RGCS, anxiety and decisional conflict. Results: Most participants (82 %, n = 63/77) made an informed choice with regard to RGCS according to our modified MMIC. Thirteen participants made an uninformed choice due to insufficient knowledge and one participant because of insufficient knowledge and value-inconsistency. Anxiety scores were elevated for three participants. Two participants presented with decisional conflict. Conclusion: Our results show high rates of informed choice among non-pregnant couples who were offered RGCS in a research study and received up to 30 min of pre-test counseling. Practice implications: Limited resources outside a research context may impact informed choice. Pre-test counselling initiatives for RGCS should ideally be organized in such a way that information can be provided at multiple time points to avoid information overload and to allow for a reflection period. Highlights: RGCS can identify couples at risk of conceiving a child with a genetic condition. Informed choice in RGCS is seen as an important evaluation criterion. High levels of informed choice can be obtained in a controlled research setting. Limited resources outside a research context may impact informed choice.